Greater Susceptibility for Metabolic Syndrome in Pediatric Solid Organ and Stem Cell Transplant Recipients. Issue 11 (November 2019) - Blöte, Ricarda; Memaran, Nima; Borchert-Mörlins, Bianca; Thurn-Valsassina, Daniela; Goldschmidt, Imeke; Beier, Rita; Sauer, Martin; Müller, Carsten; Sarganas, Giselle; Oh, Jun; Büscher, Rainer; Kemper, Markus J.; et al.
Abstract : Background: Cardiovascular comorbidity is of increasing importance after transplantation. Metabolic syndrome (MS) contributes to the risk for cardiovascular sequelae. Our aim was to assess the risk for MS in pediatric solid organ and stem cell transplant recipients by comparing them with matched untransplanted peers in a multicenter study. Methods: We prospectively assessed MS in 295 pediatric transplant recipients and compared them with 1475 age- and sex-matched controls. Results: Posttransplant metabolic syndrome (PTMS) was most frequent in lung (43%) and kidney (39%), followed by liver (16%) and stem cell (13%) recipients, compared with nontransplanted peers (4%; P < 0.01). The risk of displaying PTMS was almost 22-fold higher after lung (95% confidence interval, CI, 8.2-57.4), 16-fold higher after kidney (95% CI, 9.1-28.9), 5-fold higher after liver (95% CI, 2.1-10.1), and 4-fold higher after stem cell (95% CI, 1.4-9.5) transplantation. The contribution of individual components leading to MS differed depending on transplant type. In the combined analysis of all transplant groups, older age, less physical activity, calcineurin or mammalian target of rapamycin inhibitor-based immunosuppression, and hypovitaminosis D were associated with PTMS. Conclusions: By investigating a large group of patients, our study not only shows a high prevalence of PTMS but also identifies kidney and lung transplant patients as being at a particularly high risk. Moreover, knowledge on the factors associated with PTMS allows for individualized treatment approaches as well as potential preventive measures. Abstract : Supplemental Digital Content is available in the text.